Changes in Central Corneal Thickness and Central Macular Thickness following Uncomplicated Small-incision Cataract Surgery - Parajuli, Sanket; Sharma, Sadhana; Shrestha, Ruchi; Chapagain, Senny (Nepalese Journal of Ophthalmology, 2023)
Introduction: Cataract surgery is an invasive procedure that causes mechanical and inflammatory insult to the eye. Objectives: The objective was to study the changes in central corneal thickness (CCT) which is an indirect indicator of corneal endothelial dysfunction and the changes in macular thickness following uncomplicated small incision cataract surgery (SICS) Materials and methods: This was a prospective observational study with a before-and-after design conducted in Reiyukai Eiko Masunaga eye hospital, Banepa, Kavrepalanchok, Nepal. SICS was performed on 68 eyes of 62 patients. Change in CCT and central macular thickness (CMT) from baseline was observed post-surgery on the first day, one week, and six weeks. Results: There were 27 (43.5%) females and 35 males (56.5%) in the study. Mean age was 58.26 ±10 years. This difference of visual acuity between pre and post-operative state was statistically significant. The first post-operative day (POD) and first week post-operative CCT values when compared with preoperative CCT values were statistically significant. However, post-operative CCT values at six weeks were similar to preoperative values. Also, the differences at day one, first week and six weeks post-operative CMT values when compared with preoperative CMT values were statistically significant. Conclusion: This study revealed that there is a significant rise in CCT after SICS which gradually tends to normalize at six weeks. Similarly there is a gradual rise in CMT after SICS persisting even at six weeks. These changes were subtle and there was a marked improvement of visual acuity at six weeks after SICS.